On the features of crystallization methods used for the purification of aqueous solutions of cesium iodide - Cherginets, V.L.; Ponomarenko, T.V.; Rebrova, T.P.; Varich, A.G.; Rebrov, A.L.; Datsko, Yu.N. (Functional Materials, 2018)
Comparative analysis of CsI purification methods: mass crystallization with natural cooling (MC), low-temperature directed crystallization without stirring (LTDC/ws) and low-temperature mixed crystallization (LTMC) is presented. The MC routine possesses the highest cooling rate (6-10°C/h) and the smallest effective purification coefficients (β = 0.07-0.2) from Na, K and Rb, however the yield of the product per stage is only 60 %. The low-temperature methods are characterized by low cooling rate of ~1°C/h and higher yields of the purified product per stage (95-97 %) and β values closer to 1 than those for MC; the purification occurs especially hardly in the case of LTDC/ws (β ~ 0.9).The mentioned crystallization methods do not provide the removal of Tl which is accumulated in the product. With respect to efficiency of the purification 1 stage of MC is equivalent to 3-4 stages of LTMC or 10-11 stages of LTDC/ws and the yield of the product (CsI) is 60 %, 85-90 % and 55-70 %, respectively. The LTMC method seems the most promising for the obtaining of extra pure CsI of enhanced quality due to low enough values of β for Na, K and Rb (β = 0.46-0.6) and considerably smaller than in the case of MC rate of cooling (a degree of overcooling).